ENTREPRENEURIAL CULTURE IN THE BUSINESS FIELD - Liz Mariela Rojas Rolón, Aida; Macarena Gavilán Fleitas, Laura; Adán Báez Enciso, Miguel (Revista Gênero e Interdisciplinaridade, 2023)
The present study has proposed as objective to analyze conditions to apply entrepreneurial culture in the business environment today. And to guide this research on the proposed topic, it is because there has been a high interest focused on the entrepreneurial culture so that it is useful to apply in new business models because the old models are losing their recognition and are declining over time. time, either because of the new realities that it currently presents, for which it is essential that the innovations that occur in the commercial field, be achieved to advance from the perspective of the entrepreneurial culture. Methodologically, the present investigation has been of a quantitative approach, of a descriptive level, based on a non-experimental design, to obtain the field data, company administrators with workplaces in Ciudad del Este have been selected, randomly choosing fifteen (15) managers of companies in which the following results have been obtained: It has been possible to demonstrate that from the content analysis of the research results it was possible to identify that it is generally the administrator of the company who is responsible for developing an entrepreneurial culture that is also innovative for the company and in fact should be developed within an advance in the culture of entrepreneurship, firstly within the company, this allows working to strengthen the dynamics of resources, capacities and competencies that it has to achieve, generate knowledge and a strategic perspective, as well as an organizational one founded on the contributions of globalization to exploit new opportunities that economically generate value for the company.